Kebiasaan Membaca Novel Bahasa Inggris dan Kemampuan Mahasiswa Menerjemahkan Teks Inggris-Indonesian: Studi korelasi - Rismayanti, Rika; Meisuri; Syamsiah, Nur (FKIP, Universitas Lakidende Unaaha, 2024)
This research investigates the correlation between students’ habits of reading English novels and their ability to translate from English to Indonesian. A preliminary study involving 61 students revealed that 33 of them encountered difficulties in English-Indonesian translation, particularly in selecting appropriate vocabulary and constructing sentences that accurately convey the meaning of the original text. The study aims to determine whether a consistent habit of reading English novels influences translation proficiency among students. The research employed a correlational design and focused on fifth-semester students from the English Education Department at UIN Raden Intan Lampung. A sample of 61 students was selected randomly. Data collection involved a questionnaire with 20 items assessing students’ reading habits in English novels and a translation test to evaluate their proficiency in English-Indonesian translation. Statistical analysis using SPSS and the Pearson Product Moment formula indicated a significant positive correlation (rcount = 0.619, rtable = 0.248, N = 61, p < 0.05) between students’ reading habits and their translation abilities. This finding supports the hypothesis (Ha) that there exists a meaningful relationship between regular English novel reading habits and proficiency in English-Indonesian translation.